An overview of COVID-19 aerosol box for preventing droplet and aerosol contaminations in healthcare providers performing airway intubation. (2nd November 2021) - Li, Yan; Fu, Yujun; Zhang, Yunwei; Yu, Shuai; Luo, Jinhong; Li, Yuanyuan; Wang, Caihong; Zhu, Jingjing; Li, Huiling
Abstract: The COVID-19 is caused by the SARS-CoV-2, which is extremely infectious. Numerous virologist suggestions and guidelines advised using P2/N95 masks, gloves, goggles, face-shields, and frocks or gowns as routine specific protective tools during airway management to protect healthcare personnel from infection (PPE). However, numerous imitation research has indicated that conventional PPE cannot adequately protect healthcare personnel. Since then, numerous firms and healthcare professionals have created their personal reformed devices 'aerosol containment devices' (ACD). Their usage has expanded throughout the world without being properly evaluated for usefulness, efficacy, or safety. The practice of 'ACD' has been shown to make tracheal intubation (TI) more problematic in several simulated tests. Furthermore, the device should limit the transmission of droplets from a patient; however, it might put healthcare personnel at danger of being exposed to greater levels of viral aerosols. Consequently, the existing state of information suggests that 'ACD' deprived of a vacuum mechanism can simply protect healthcare personnel against viral transmission to a limited extent. We search various databases for the literature with keywords 'COVID-19, ' 'aerosol box, ' 'aerosol contaminations, ' and 'droplet contaminations.' The current review focused on the aerosol box from various perspectives, including their mechanism, optimum time of use, the spread of aerosol control, current gaps, and future perspective for bridging those gaps.